Tribological behaviour of hypereutectic Al-Si automotive cylinder liner material under dry sliding wear condition in severe wear regime. (July 2021) - Baby, Ajith Kurian; Priyaranjan, M; Deepak Lawrence, K; Rajendrakumar, PK
Hypereutectic Al-Si alloys are used as material for the engine block and cylinder liners in automobiles. Wear behaviour of hypereutectic Al-Si alloy system changes significantly with applied normal load in both mild wear and severe wear regime. Significant improvement in wear resistance can be obtained by exposing silicon particles through the chemical etching process. For Al-25% Si alloys, most studies are reported in mild and ultra-mild wear regime. In the present work, the wear of exposed silicon particles with varying load and speed in severe wear regime was investigated under the unidirectional sliding condition and bi-directional sliding condition using a pin-on-disk tribometer (POD) and a linear reciprocating tribometer (LRT), respectively. Rapidly solidified and T6 heat-treated Al-25Si alloy was polished and etched using 5% NaOH solution to expose the silicon particles. Experiments were carried out with normal loads varying from 40 N to 120 N in dry sliding conditions. Sliding speeds of 0.8 m/s and 1.5 m/s were applied for each load in case of a pin on disk tribometer whereas, in an LRT, the sliding velocities were 0.2 m/s and 0.45 m/s respectively for each set of the load. The surface topography was measured by means of a 3-D optical profilometer, and surface morphology was analyzed using SEM images. It was observed that at higher loads, larger Si particles were fractured and pushed into the matrix. Fractured silicon particles, along with smaller particles, were embedded into the matrix, thereby increasing the silicon concentration in the wear region. The comparison of the experimental results of unidirectional and bi-directional sliding that reveal the change in surface morphology of silicon particles, the friction characteristics at the interface, variation of surface 3-D roughness parameters, the wear rate and wear mechanisms of Al-25% Si alloys are analyzed and reported in the study.